ANALYSIS OF REQUIREMENTS FOR CHILDREN'S CLOTHES (American Journal of Business Management, Economics and Banking, 2022)
In the article, marketing research was conducted in local markets of Namangan region and district for the production of a set of girls' clothes, and consumer demand was studied. Based on the results of the research, it was analyzed that there is a high demand for national adras fabric models sewn for children's clothes with simplicity, various kant, core stitches, zippers.